2-azido-2-deoxy-2,4-C-dimethyl-3,4-O-isopropylidene-L-ribono-1,5-lactone - Booth, K; Watkin, D; Jenkinson, S; Fleet, G (2007)
The relative configuration of the title lactone, C10H15N3O4, a compound of value in the synthesis of complex pyrrolidines, was determined by X-ray crystallographic analysis. © International Union of Crystallography 2007.